Enhancement of Astroglial Aerobic Glycolysis by Extracellular Lactate-Mediated Increase in cAMP - Vardjan, Nina; Chowdhury, Helena H.; Horvat, Anemari; Velebit, Jelena; Malnar, Maja; Muhič, Marko; Kreft, Marko; Krivec, Špela G.; Bobnar, Saša T.; Miš, Katarina; Pirkmajer, Sergej; Offermanns, Stefan; et al. (Frontiers in Molecular Neuroscience, 2018)
Besides being a neuronal fuel, L-lactate is also a signal in the brain. Whether extracellular L-lactate affects brain metabolism, in particular astrocytes, abundant neuroglial cells, which produce L-lactate in aerobic glycolysis, is unclear. Recent studies suggested that astrocytes express low levels of the L-lactate GPR81 receptor (EC50  5 mM) that is in fat cells part of an autocrine loop, in which the Gi-protein mediates reduction of cytosolic cyclic adenosine monophosphate (cAMP). To study whether a similar signaling loop is present in astrocytes, affecting aerobic glycolysis, we measured the cytosolic levels of cAMP, D-glucose and L-lactate in single astrocytes using fluorescence resonance energy transfer (FRET)-based nanosensors. In contrast to the situation in fat cells, stimulation by extracellular L-lactate and the selective GPR81 agonists, 3-chloro-5-hydroxybenzoic acid (3Cl-5OH-BA) or 4-methyl-N-(5-(2-(4-methylpiperazin-1-yl)-2-oxoethyl)-4-(2-thienyl)-1,3-thiazol-2-yl)cyclohexanecarboxamide (Compound 2), like adrenergic stimulation, elevated intracellular cAMP and L-lactate in astrocytes, which was reduced by the inhibition of adenylate cyclase. Surprisingly, 3Cl-5OH-BA and Compound 2 increased cytosolic cAMP also in GPR81-knock out astrocytes, indicating that the effect is GPR81-independent and mediated by a novel, yet unidentified, excitatory L-lactate receptor-like mechanism in astrocytes that enhances aerobic glycolysis and L-lactate production via a positive feedback mechanism.